2002
DOI: 10.1037/1089-2680.6.4.325
|View full text |Cite
|
Sign up to set email alerts
|

Victimization and Substance Abuse among Women: Contributing Factors, Interventions, and Implications

Abstract: Although the literature indicates that there is an association of victimization with substance abuse, there has been limited research focused on understanding and synthesizing the factors that have been identified as contributing to victimization and substance abuse and on interventions designed to address these contributing factors. The purposes of this article are to (a) review the literature on factors related to victimization and substance abuse, (b) review interventions and outcomes, and (c) discuss clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(136 citation statements)
references
References 712 publications
5
127
2
2
Order By: Relevance
“…The rate of violent episodes involving alcohol intake corroborates other studies carried out in Brazil and other countries. 6,8,17,20,21,24 The different forms of violence associated to alcohol use found in the present study have also been described in the literature. Studies have showed that episodes of domestic violence involving alcohol use tend to be more severe and increase the likelihood of co-occurrence of other forms of violence.…”
Section: Discussionsupporting
confidence: 52%
“…The rate of violent episodes involving alcohol intake corroborates other studies carried out in Brazil and other countries. 6,8,17,20,21,24 The different forms of violence associated to alcohol use found in the present study have also been described in the literature. Studies have showed that episodes of domestic violence involving alcohol use tend to be more severe and increase the likelihood of co-occurrence of other forms of violence.…”
Section: Discussionsupporting
confidence: 52%
“…In an American study, over 50% of women with mental health disorders had a co-occurring substance use problem, and nearly all were rooted in histories of trauma (Fallot & Harris, 2004). Alcohol abuse can be up to 15 times higher for women who are victims of partner violence than women who are not victims (Logan, Walker, Cole, & Leukefeld, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While drug abuse is the result of a complex interplay of biochemical, psychological, social, and environmental factors, genetic variance plays an important role in the susceptibility of adolescents' drug use and abuse. It is also claimed that the more severe the abuse, the greater the role of genetic factors (Crabbe 2002 ;Logan et al 2002 ). While social and environmental factors may determine whether an adolescent is exposed to drugs, genetics may help to explain why only some of those adolescents who are exposed use and abuse drugs.…”
Section: Genetic Predispositionmentioning
confidence: 99%